The chosen. Season four [videorecording (DVD)] - Jenkins, Dallas; Swanson, Ryan (Screenwriter); Thompson, Tyler (Screenwriter); Tabish, Liz, 1986-; Shakoour, Nick; Ross, Jordan Walker, 1990-; Patel, Paras; Roumie, Jonathan, 1974-; Isaac, Shahar; James, Noah; Xanthis, George Harrison; Sharma, Shaan; et al. (The Chosen, 2024)
Clashing kingdoms, Rival rulers. The enemies of Jesus close in for the kill while His followers struggle to keep up, leaving Him to carry the burden alone. Season Four promises to deliver where last season₂s incredible walking on-water finale left off.